The Onset of Systemic Lupus Erythematosus Triggers Nucleus Pulposus Cell Pyroptosis to Exacerbate Intervertebral Disc Degeneration - Lao Z; Fang X; Shen S; Zhang Y; Chen X; Zhang H; Bian Y; Zhou C; Bao R; Xu T; Jin H; Fu F; et al. (Dove Medical Press, 2024)
Zhaobai Lao,1,* Xuliang Fang,1,* Shuchao Shen,1,* Yuliang Zhang,2,* Xin Chen,1 Helou Zhang,1 Yishan Bian,1 Chengcong Zhou,1 Ronghua Bao,2 Taotao Xu,3 Hongting Jin,1 Fangda Fu,1 Chengliang Wu,1 Changfeng Hu,4 Hongfeng Ruan1 1Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Traditional Chinese Medicine), Hangzhou, Zhejiang, 310053, People's Republic of China; 2Hangzhou Fuyang Hospital of TCM Orthopedics and Traumatology, Hangzhou, Zhejiang, 311400, People's Republic of China; 3Department of Orthopaedics, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Traditional Chinese Medicine), Hangzhou, Zhejiang, 310053, People's Republic of China; 4College of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People's Republic of China*These authors contributed equally to this workCorrespondence: Changfeng Hu, College of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People's Republic of China, Email zhudianzhuifeng@163.com Hongfeng Ruan, Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, 548 Binwen Road, Hangzhou, 310053, People's Republic of China, Email rhf@zcmu.edu.cnPurpose: Systemic lupus erythematosus (SLE) is an autoimmune disorder marked by immune system dysregulation and autoantibodies production, causing widespread inflammation and damage across various body systems. Despite the prevalent back pain in SLE patients, the link between SLE and intervertebral disc (IVD) degeneration, a primary contributor to back pain, remains inadequately understood. This study explored the impact of SLE on IVD degeneration using the MRL/lpr mouse model, which effectively replicates human SLE manifestations.Methods: The study utilized MRL/lpr mice to investigate the effects of SLE on IVD degeneration. The mice were evaluated for typical SLE phenotypes and indicators of IVD degeneration, including IVD height, IVD score, tissue integrity, extracellular matrix degradation, and apoptosis of IVD cells. Additionally, the study examined nucleus pulposus (NP) pyroptosis and inflammatory cytokine secretion. Mechanistic analysis focused on the antioxidant pathway, specifically the expression levels of NRF2, HO-1, KEAP1, and the phosphorylation levels of p65.Results: MRL/lpr mice displayed typical SLE phenotypes and exacerbated profiles of IVD degeneration, including reduced IVD height, lower IVD score, significant IVD tissue impairment, extracellular matrix degradation, and increased apoptosis of IVD cells. Notably, SLE stimulated NP pyroptosis and excessive secretion of inflammatory cytokines. Mechanistic analysis indicated that the progression of SLE impedes the antioxidant pathway by downregulating NRF2 and HO-1 expression, upregulating KEAP1, and enhancing phosphorylation levels of p65.Conclusion: Our findings highlight the mechanistic link between SLE and IVD degeneration, suggesting potential therapeutic targets for mitigating back pain in SLE patients.Keywords: systemic lupus erythematosus, intervertebral disc degeneration, nucleus pulposus, pyroptosis, NRF2/KEAP1/NF-κB pathway